PENGARUH KONSUMSI, HARGA ECERAN DAN GROSS DOMESTIC PRODUCT (GDP) PER KAPITA TERHADAP IMPOR GULA PASIR DI INDONESIA - Ansori, M. Subra; Usman, Umaruddin; Andriyani, Devi; Abbas, Tarmizi (Jurnal Ekonomi Pertanian Unimal, 2024)
This research aims to determine the influence of consumption, retail prices and GDP per capita on sugar imports in Indonesia. The data used in this research is secondary data in the form of a time series for 1990-2022 obtained from the world bank and BPS (Central Statistics Agency). The data analysis method uses the Error Correction Model (ECM) approach, where the conditions for using this model are that all variables must be stationary first differences, have at least one cointegration equation and have a negative ECT (Error Correction Term) value so that the model is valid and can be used. The results show that in the short term consumption is not significant on sugar imports in Indonesia, while in the long term consumption has a negative and significant effect on sugar imports in Indonesia. The retail price variable has no effect on sugar imports in Indonesia in the short term, and in the long term retail prices have a positive and significant effect on sugar imports in Indonesia. The GDP Per Capita variable, both in the short and long term, has no effect on sugar imports in Indonesia.